The use of neurovascular ultrasound versus digital subtraction angiography in acute ischemic stroke - Marcos C. Lange (Arquivos de Neuro-Psiquiatria, 2015)
Cervical and intracranial arterial evaluation is an important issue for acute ischemic stroke (IS). Objective Compare the use of the neurovascular ultrasound examination (NVUE) to digital subtraction angiography (DSA) in acute IS patients for diagnosing significant extracranial and intracranial arteriopathy. Method Nonconsecutive patients with IS or transient ischemic attack admitted within 12 hours of the onset of symptoms were evaluated retrospectively. Standardized NVUE and DSA were done in all patients within the first 120 hours of hospital admission. Results Twenty-four patients were included in the study. Compared to DSA, the NVUE demonstrated 94.7% sensitivity and 100% specificity for identifying symptomatic extracranial and/or intracranial arteriopathy. Conclusion The standardized NVUE technique demonstrated high sensitivity and specificity compared to DSA for diagnosing arterial abnormalities in acute IS patients.